Medication Safety in Neonates - Dabliz, Rabih; Levine, Stuart (American Journal of Perinatology, 2012)
Newborn intensive care units (NICUs) are high-risk areas of care, where complex medical interventions are performed, and are recognized as a resource for improved outcome in premature and low-birth-weight infants or those presenting with acute conditions. This critical environment, along with the vulnerable nature of the population it serves, places patients at risk for medication errors, which can result in permanent harm or death. Promoting safe medication practices requires participation of all individuals involved in the medication use process (e.g., physicians, nurses, nurse practitioners, physician assistants, pharmacists, respiratory therapists, pharmacy technicians). The following recommendations, organized in accordance with the Institute for Safe Medication Practices' Key Elements of the Medication Use System™, will focus on significant areas of concern within the NICU. All individuals caring for neonates, supported by administrators and organizational leaders, should recognize themselves as active partners responsible for the safety of this fragile patient population by participating in the design and sustainment of a safe and efficient medication use system.
Keywords: neonates; medication error; adverse drug event; high alert